Fight against jihadist terrorism and the rule of law - Belaúnde Matossian, Francisco (2021)
Jihadist terrorism represents a huge challenge on a global scale. Due to its characteristics, it is very difficult to combat, and it puts the rule of law to the test in various parts of the world. In Europe, the United States and other countries, a series of legal measures and devices have been adopted to grant a greater margin of action to the authorities, be they police, administrative or jurisdictional. In some way, a regulatory siege against terrorism has been taking place. The dilemma of the limits of this activism then arises, insofar as it can lead to crossing the borders of the rule of law and violating fundamental rights. In fact, in several cases, this is what has happened according to human rights defenders and other actors.